Investigating the Influence of Employee Engagement and Supporting Factors Towards Organizational Performance: A Systematic Literature Review - Rahel Sibatuara; Meyvanali; Manalu, Della Edelweiss (Universitas Pelita Harapan, 2024)
This study aims to find out the influence of employee engagement towards organizational performance. Many factors, such as work motivation and job engagement appear to strengthen employee engagement and affect organizational performance. The method used is through a comprehensive review of relevant literature and empirical studies. The results of the study indicate various factors, including employee engagement, work motivation, job engagement, and affecting the organization performance. The results indicate that cultivating a culture of participation must be a strategic focus for organizations seeking long-term success in a competitive global environment. In conclusion, improving employee engagement is crucial for organizational development and effectiveness.